Comments on Bahlburg (2021), A Silurian-Devonian active margin in the proto- Andes –new data on an old conundrum: International Geology Review doi.org/10.1080/00206814.2021.2012719. Issue 3 (4th February 2023) - Dahlquist, Juan A.; Morales Cámera, Matías M.; Alasino, Pablo H.; Pankhurst, Robert J.; Rapela, Carlos W.; Moreno, Juan A.; Baldo, Edgardo G.; Rocher, Sebastián
ABSTRACT: We clarify some statements on our works included by Bahlburg (2021), which we think are confusing and misleading. Clarification is highly necessary to interpreting the evolution of the Devonian proto-Andean margin of Argentina and Chile, and in this work, we show that this clarification is appropriated and should be considered.